Visual self-assessment of dental appearance: A comparison of mirror types and digital reflection via smartphone front facing camera - Al Imran Shahrul; Asma Ashari; Ratnah Thevi Subramanam (PLoS ONE, 2026)
Introduction In dental practice, patients often evaluate their own dental attractiveness using mirrors or smartphone digital reflections. This study aimed to investigate how mirror size, shape, magnification and smartphone-based digital reflection influence self-perceived dental attractiveness. Materials and methods This was a prospective cross-sectional study. Eighty-three participants assessed their dental attractiveness using a randomised sequence of reflective devices, including mirrors of different sizes (full-length, medium, small, standard pocket), a magnified pocket mirror, a tooth-shaped mirror, and a smartphone front-facing camera. Ratings were recorded on a 10-point visual analogue scale. Data were analysed using repeated-measures ANOVA with Bonferroni-adjusted post hoc comparisons. Intra-rater reliability was evaluated in a subset of participants using the intraclass correlation coefficient (ICC). Results Repeated-measures ANOVA indicated a significant overall effect of device type on dental attractiveness (F(4.62, 378.83) = 15.57, p < 0.001). Post hoc analyses showed no significant differences among full-length, medium, small, and standard pocket mirrors, or between these mirrors and the smartphone reflection (all p > 0.05). The magnified pocket mirror and tooth-shaped mirror were rated significantly lower than other devices (p < 0.001). Intra-rater reliability was generally poor (ICC < 0.35), with only the medium-size and tooth-shaped mirrors showing moderate agreement (ICC = 0.59 and 0.63, respectively). Conclusion Reflective device type influences self-perceived dental attractiveness. Standard mirrors of different sizes and smartphone reflections produced similar and generally favourable ratings. In contrast, magnified and tooth-shaped mirrors yielded lower ratings. Poor intra-rater reliability suggests that self-assessment based on reflection alone is inconsistent.